The Implementation of Suggestopedia Method in Arabic Teaching for Qirā’ah - Yogia Prihartini; Wahyudi Buska; Nur Hasnah Nur Hasnah (INNOVATIO: Journal for Religious Innovation Studies, 2019)
This research is meant to find that qirā’ah is one of important factors to see Arabic achievement as well as istimā’, kalām and kitābah. Other factors are from the methods of teaching like: TPR (Total Physical Response), Silent way, and Community Language Learning and suggestopedia method. In this paper the writer limits the problem by focusing on teaching qirā’ah descriptive paragraph through suggestopedia method. The writer formulates the problem of this paper. The formulation is "How does the teacher teach descriptive paragraph through suggestopedia to senior high school students at State Islamic Senior High school (MAN) Model jambi”. This paper is significant because it will be very useful for senior high school students, Its hoped that when the teachers apply the suggestopedia method, the students can learn qirā’ah in more enjoyable and fun environment. This paper is also important for teachers. It is hoped that they will have wider and deeper understanding of teaching methods in general, particularly suggestopedia method in teaching qirā’ah.